Die Stumme von Portici - Zinke, Johann Wenzel, 1797-1858 (engraver):::Creator::::::::::::; Schoeller, Johann Christian, 1782-1851 (artist):::Contributor:::::::::::: (Vienna; Austria; Wiener Allgemeine Theaterzeitung, 2021)
Copper engraving of a scene from Daniel Auber's opera La muette de Portici, by Zinke based on Schoeller.